HUBUNGAN AKTIVITAS BERMAIN DENGAN STATUS GIZI ANAK USIA DINI (4-6 TAHUN) DI PUSKESMAS BANYUGLUGUR - Agustinah, Henni; Sary, Yessy Nur Endah; Ekasari, Tutik (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Playing is an activity that children do to make something fun.Playing can affect physical development communication drive channelling pent-up emotional energy channelling for needs and desires learning resources stimulation for creativity developing self-insight learning societal moral standards learning to play according to gender roles development of desired personality traits.Good nutritional intake with a healthy diet can also generate additional energy to use in daily activities.On the other hand,malnutrition results in a lack of substances the body needs so that it is susceptible to disease,in addition,it affects growth,physical health,body functions,behaviour and even mood.The purpose of this study was to determine the relationship between play activity and the nutritional status of early childhood (4-6 years) at the Banyuglugur Health Center. The research design is cross sectional. The population in this study were all children aged 4-6 years at the Banyuglugur Health Center as many as 216 people. The sample is 4-6 years old children at the Banyuglugur Health Center as many as 47 people using a purposive sampling technique. The instruments used were a play activity questionnaire and an observation sheet in the MCH book. Based on the Sperm statistical test, it is known that the P Value is 0.513 with an α of 0.05. Because the significance value is <α, then H1 is rejected, H0 is accepted, which means that there is a relationship between play activity and the nutritional status of early childhood (4-6 years) at the Banyuglugur Health Center. It is hoped that the results of this study can be used as input for people who have children aged 4-6 years.